Instructional design based on social learning and TPACK to improve language learning - Montoya Muñoz, Gabriela Emma Edith (2020)
Technology plays a significant role in education nowadays. People is aware of its importance and there are numerous researches regarding its benefits when applied to the teaching – learning process. Nevertheless, since social networks are a relatively young developed technology, few researches have been carried out around the world about it, and virtually none in Peru. This research was developed with the sole purpose of analyzing the impact that the application of an instructional design based on social learning theory and TPACK framework has on promoting the use of social network sites to improve English language learning of students coursing Beginners IV at Señor de Sipan Language Center (SSLC) during October 2015. To test the hypothesis the quasi experimental design was applied. A Pre - test was given, to diagnose the problem. Results shown that students had a low level of English language learning, they were not capable of communicating in the target language even at a basic level. Further research was carried out, to dig deeper into the problem and after applying an interview and questionnaire to the teachers, it was possible to spot the problem: Activities, strategies and methods, applied in most classes were traditional and left behind the proper use of any technology. Classes did not meet students interests and did not engage their participation. Results were encouraging, after the application of the Post - test it was possible to note the improvement of students’ level and interest for their English classes.